Antibiotic susceptibility profile of Vibrio parahaemolyticus isolated from shrimp in Selangor, Malaysia - Gargouti, Saifedden Ayad; Mohamad Ghazali, Farinazleen; Mahmud @ Ab Rashid, Nor Khaizura; Kayali, Ahmad Yaman; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Vibrio parahaemolyticus is a halophilic Gram-negative bacterium that is considered among gastrointestinal pathogens. Thirty isolates were tested for their susceptibility using 14 different antibiotics. One V. parahaemolyticus isolate was resistant to 10 antibiotics (cefotaxime, ceftazidime, tetracycline, amikacin, ciprofloxacin, levofloxacin, ofloxacin, ampicillin, amoxicillin-calv-acid, and cefepime). The V. parahaemolyticus isolates were resistant to ampicillin (90%), amoxicillin-clavulanic acid (63.3%), cefotaxime (60%), ceftazidime (46.7%), cefepime (50%), tetracycline (36.6%), and amikacin (26.7%). However, the isolates were highly susceptible to imipenem (100%), and piperacillin and gentamicin (96.7%). Approximately 55% of the isolates showed a multiple antibiotic resistance (MAR) index of > 0.2, thereby indicating the high risk of sources where these isolates originated. The occurrence of MAR asserted the importance of determining drug susceptibility and monitoring the antimicrobial resistance profile to improve and ensure food safety and public health.